(3JbQjQGJ abgjIs - (3GdCUagGfj, abjg GdadGSaI, eMeO MSjf Hf eMeO MSf, J (B1361 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B.. (3dG ETcGd aj Cf eG Hjf RhGd GdTeS Edi ZQQ HgG hbYJ ddXgQ hGdYUQ HdG NdGa ajg aj GdLedI hEfeG GdETcGd aj (B.. (3eTJQcGf aj LejY GdhbJ ZGjI GdCeQ (B...s
(3BNQgG (B:s
... (3gPG cdg HMSH GdbGYOI eY YOe chf YGOI aj Gdjbjf hEdG aGdYGOI Jchf HefRdI GdTQW agj eJHYI Odjd GdUHZ hGdeOGO hCeKGdgeG aj Ref hGdCRefI Jchf ef gPG GdbHjd ceG dG jNais
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6/106s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis